The perspective of youth: envisioning transformative pathways and desirable futures for people and nature - Thomas M. Schmitt; Juliette Aminian-Biquet; Polina Blinova; Yohana G. Jimenez; Lider Sinav; Hana Vašková; Ana Sofia Lorda Dumont; Pham Trung Kien; Vinamra Mathur; Brenda Mwale; Deign Frolley Soriano; Nopparat Anantaprayoon; et al. (Sustainability Science, 2025)
This paper examines the pathways to desirable nature futures as envisioned by 22 young people from all United Nations regions and diverse cultural backgrounds who participated in the second edition of the IPBES Youth workshop (2022). The workshop employed the Three Horizons framework and the Nature Futures Framework (NFF) to describe the plurality of youth visions for desirable nature futures and transformative pathways to achieve these visions. Based on the outcomes of the workshop, we conducted a qualitative content analysis categorizing the ideas and quantitatively assessed commonalities and differences among workshop groups, which were based on the NFF perspectives (nature for nature, nature for society, nature as culture, and a group in between perspectives). There were important differences in the visions and pathways articulated by the groups, but also commonalities, such as the importance of governance, community-based approaches, and education for achieving desirable nature futures. We also discuss the importance of flexibility in the NFF to accommodate diverse perspectives and involvement of youth in shaping global sustainability agendas. While many ideas raised by young people during this workshop align with existing conservation narratives, the study reveals the need to foster new and innovative ideas to drive transformative change that is sensitive to diverse contexts, histories, and experiences.

Exploring component traits of biomass and yield in Indian rice mini-core germplasm - Chandrapal Vishwakarma; Sourabh Karwa; Riti Thapar Kapoor; Komal Mathur; G. K. Krishna; Rakesh Pandey; Ranjith K. Ellur; Gopalakrishnan Subbaiyan; K. K. Vinod; Viswanathan Chinnusamy (Plant Physiology Reports, 2024)

Assessment and Threat to Significant Geoheritage of Soorsagar Formation of Jodhpur Group of Marwar Supergroup, Western Rajasthan, India: A Geological and Remote Sensing Approach - Saurabh Mathur; Sudhanshu Sharma; S. K. Singh; M. G. Thakkar; Gaurav Chauhan; Shiv Singh Rathore; S. C. Mathur (Geoheritage, 2023)

S17-02: The Long-term Impact of Perinatal Exposures on Susceptibility to Immune-mediated Diseases - K.A. Rychlik; E.J. Illingworth; S.E. Attreed; S.S. Sanchez; A. Grant-Alfieri; M.C. Rodriguez Steube; A. Mathur; I.F. Sanchez; C. Tang; M. Suresh; G. Lopez-Cecetaite; P. Sadhukhan; et al. (Toxicology Letters, 2023)

A novel QTL linked to asparagine synthetase gene for stem height increment in oil palm (E. guineensis Jacq.) identified and validated through integrated genomic approaches - B. Kalyana Babu; R. K. Mathur; G. Ravichandran; P. Anitha; H. P. Bhagya; M. V. B. Venu (Euphytica, 2023)

Phenomics, genomics of oil palm (Elaeis guineensis Jacq.): way forward for making sustainable and high yielding quality oil palm - B. Kalyana Babu; R. K. Mathur; P. Anitha; G. Ravichandran; H. P. Bhagya (Physiology and Molecular Biology of Plants, 2021)

Comparing transformation pathways across major economies - R. Schaeffer; A. Köberle; H. L. van Soest; C. Bertram; G. Luderer; K. Riahi; V. Krey; D. P. van Vuuren; E. Kriegler; S. Fujimori; W. Chen; C. He; et al. (Climatic Change, 2020)

Passage survival of European and American eels at Francis and propeller turbines - Paul G. Heisey; Dilip Mathur; Joanne L. Phipps; Jerry Christopher Avalos; Cory E. Hoffman; Steven W. Adams; Eric De‐Oliveira (Journal of Fish Biology, 2019)
We present the magnitude of losses of European eel Anguilla anguilla and American eel A. rostrata in passage through propeller and Francis turbines at hydroelectric projects. Survival and injury rates and types were turbine type related. Overall, eel survival was higher (mean ± 90% CI = 95.1 ± 5.3%,) and injury rate lower (12.5 ± 10.5) at Francis than propeller turbines (survival = 80.7 ± 6.4%; injury rate = 25.7 ± 7.9%). The common injury type at Francis turbines was bruises and at propeller turbines was severance. Blade shape and thickness of the leading edge of the blades (rounded, thick buckets of Francis turbines v . flatter, sharper edged blades in propeller turbines); eel entry routes into the turbines; their flexible, cylindrical body shape and orientation probably contributed to these differences. Relationship between survival and injury and turbine characteristics was turbine specific. For Francis turbines, one negative correlation ( r = −0.986, P r = 0.740, P r = 0.835, P

Ensemble encoding of action speed by striatal fast-spiking interneurons - Bradley M. Roberts; Michael G. White; Mary H. Patton; Rong Chen; Brian N. Mathur (Brain Structure and Function, 2019)

Genome-wide association study (GWAS) for stem height increment in oil palm (Elaeis guineensis) germplasm using SNP markers - B. Kalyana Babu; R. K. Mathur; G. Ravichandran; M. V. B. Venu (Tree Genetics & Genomes, 2019)

Claustrum circuit components for top–down input processing and cortical broadcast - Michael G. White; Brian N. Mathur (Brain Structure and Function, 2018)

Frontal cortical control of posterior sensory and association cortices through the claustrum - Michael G. White; Brian N. Mathur (Brain Structure and Function, 2018)

28-Homobrassinolide: a novel oxysterol transactivating LXR gene expression - R. Premalatha; K. Srikumar; D. Vijayalaksmi; G. N. Kumar; P. P. Mathur (Molecular Biology Reports, 2014)

Erratum to: Re–Os isotope evidence for mixed source components in carbonate-replacement Pb–Zn–Ag deposits in the Lavrion district, Attica, Greece - Paul G. Spry; Ryan D. Mathur; Todd A. Bonsall; Panagiotis Ch. Voudouris; Vasilios Melfos (Mineralogy and Petrology, 2014)

Re–Os isotope evidence for mixed source components in carbonate-replacement Pb–Zn–Ag deposits in the Lavrion district, Attica, Greece - Paul G. Spry; Ryan D. Mathur; Todd A. Bonsall; Panagiotis Ch. Voudouris; Vasilios Melfos (Mineralogy and Petrology, 2014)

Pharmacological characterisation of ligand- and voltage-gated ion channels expressed in human iPSC-derived forebrain neurons - Jeffrey L. Dage; Ellen M. Colvin; Antoine Fouillet; Emily Langron; William C. Roell; Jingling Li; Sachin X. Mathur; Adrian J. Mogg; Matthew G. Schmitt; Christian C. Felder; Kalpana M. Merchant; John Isaac; et al. (Psychopharmacology, 2014)

An ecogenomic analysis of herbivore‐induced plant volatiles in B rassica juncea - Vartika Mathur; Tom O. G. Tytgat; Cornelis A. Hordijk; Harry R. Harhangi; Jeroen J. Jansen; A. Sankara Reddy; Jeffrey A. Harvey; Louise E. M. Vet; Nicole M. van Dam (Molecular Ecology, 2013)
Upon herbivore feeding, plants emit complex bouquets of induced volatiles that may repel insect herbivores as well as attract parasitoids or predators. Due to differences in the temporal dynamics of individual components, the composition of the herbivore‐induced plant volatile ( HIPV ) blend changes with time. Consequently, the response of insects associated with plants is not constant either. Using Brassica juncea as the model plant and generalist Spodoptera spp. larvae as the inducing herbivore, we investigated herbivore and parasitoid preference as well as the molecular mechanisms behind the temporal dynamics in HIPV emissions at 24, 48 and 72 h after damage. In choice tests, Spodoptera litura moth preferred undamaged plants, whereas its parasitoid Cotesia marginiventris favoured plants induced for 48 h. In contrast, the specialist Plutella xylostella and its parasitoid C. vestalis preferred plants induced for 72 h. These preferences matched the dynamic changes in HIPV blends over time. Gene expression analysis suggested that the induced response after Spodoptera feeding is mainly controlled by the jasmonic acid pathway in both damaged and systemic leaves. Several genes involved in sulphide and green leaf volatile synthesis were clearly up‐regulated. This study thus shows that HIPV blends vary considerably over a short period of time, and these changes are actively regulated at the gene expression level. Moreover, temporal changes in HIPV s elicit differential preferences of herbivores and their natural enemies. We argue that the temporal dynamics of HIPV s may play a key role in shaping the response of insects associated with plants.

Identification of quantitative trait loci associated with resistance to foliar diseases in sorghum [Sorghum bicolor (L.) Moench] - S. Murali Mohan; R. Madhusudhana; K. Mathur; D. V. N. Chakravarthi; Sanjay Rathore; R. Nagaraja Reddy; K. Satish; G. Srinivas; N. Sarada Mani; N. Seetharama (Euphytica, 2010)

Variation of Mo isotopes from molybdenite in high-temperature hydrothermal ore deposits - Ryan Mathur; S. Brantley; A. Anbar; F. Munizaga; V. Maksaev; R. Newberry; J. Vervoort; G. Hart (Mineralium Deposita, 2010)

Assessment and rationalization of genetic diversity of Papua New Guinea taro (Colocasia esculenta) using SSR DNA fingerprinting - D. Singh; E. S. Mace; I. D. Godwin; P. N. Mathur; T. Okpul; M. Taylor; D. Hunter; R. Kambuou; V. Ramanatha Rao; G. Jackson (Genetic Resources and Crop Evolution, 2008)

Improved guggulsterone production from sugars, precursors, and morphactin in cell cultures of Commiphora wightii grown in shake flasks and a bioreactor - Meeta Mathur; K. G. Ramawat (Plant Biotechnology Reports, 2008)

Guggulsterone production in cell suspension cultures of the guggul tree, Commiphora wightii, grown in shake-flasks and bioreactors - Meeta Mathur; K. G. Ramawat (Biotechnology Letters, 2007)

Land cover classification using multi‐temporal MERIS vegetation indices - J. Dash; A. Mathur; G. M. Foody; P. J. Curran; J. W. Chipman; T. M. Lillesand (International Journal of Remote Sensing, 2007)

Changes in Brain Intracellular pH and Membrane Phospholipids on Oxygen Therapy in Hypoxic Patients with Chronic Obstructive Pulmonary Disease - G. Hamilton; R. Mathur; J.M. Allsop; D.M. Forton; N.S. Dhanjal; R.J. Shaw; S.D. Taylor-Robinson (Metabolic Brain Disease, 2003)

Ameliorative effects of proline on salt stress-induced lipid peroxidation in cell lines of groundnut (Arachis hypogaea L.) - M. Jain; G. Mathur; S. Koul; N. Sarin (Plant Cell Reports, 2001)

In vitro plantlet regeneration from mature zygotic embryos of Pinus wallichiana A.B. Jacks - G. Mathur; R. Nadgauda (Plant Cell Reports, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)